Innovative use of trichantera gigantea leaves and pineapple waste as eco-friendly feed additives for enhanced tilapia growth - Sarbandi, Mimi Sophia; Mohamed, Siti Mazleena; Hashim, Saiyidah Nafisah (2025)
The rising demand for sustainable aquaculture practices has prompted the exploration of alternative, eco-friendly feed additives to support fish growth while reducing environmental impacts. This study investigates the effects of incorporating Trichanthera gigantea and pineapple waste as feed additives in the diets of juvenile tilapia (Oreochromis niloticus). To the best of our knowledge, this is the first study to examine the combined use of these two plant-based ingredients in tilapia nutrition. Four experimental diets were formulated, with varying inclusion levels of T. gigantea and pineapple waste, and their effects on weight gain, growth performance, and feed conversion ratio (FCR) were assessed for 28 days in controlled aquaculture tanks. Among the tested formulations, the diet containing 10% pineapple waste and 10% T. gigantea yielded the most favorable FCR of 1.25, indicating improved feed efficiency without compromising fish growth. To our knowledge, this is the first study to report on the effects of a combined diet of Trichanthera gigantea and pineapple waste as feed additives in tilapia juveniles (Oreochromis niloticus), demonstrating a novel and potential stage-specific nutritional approach in sustainable aquaculture. This synergistic use of agro-industrial and plant-based waste presents a cost-effective and environmentally sustainable strategy for aquaculture. The findings support the potential of utilising local, underused bioresources to promote circular economic practices in fish farming, aligning with global goals for sustainable food production.